hCG values and gestational sac size as indicators of successful systemic methotrexate treatment in cesarean scar pregnancy - Takashi Mitsui; Sakurako Mishima; Akiko Ohira; Kazumasa Tani; Jota Maki; Eriko Eto; Kei Hayata; Hisashi Masuyama (Elsevier, 2021)
Objective: To retrospectively investigate cesarean scar pregnancy (CSP) patients who received systemic methotrexate (MTX) and to clarify the criteria for administering systemic MTX to CSP patients. Materials and methods: Fifteen CSP patients who were initially treated with systemic MTX (50 mg/m2/week) were included. Nine patients, who needed a uterine artery embolization (UAE) or a laparotomy, including a transabdominal hysterectomy (TAH), were defined as the unsuccessful MTX group. Six patients who did not require UAE or a laparotomy were defined as the successful MTX group. Furthermore, the hCG cut-off value and the GS cut-off size at the time of CSP diagnosis, which differentiated successful and unsuccessful patients, were defined. MTX success rates were investigated by combining the hCG and gestational sac (GS) size cut-off values. Results: The hCG cut-off value was 17757.0 mIU/mL, and the GS cut-off size was 10.4 mm. In patients with hCG values less than 17757.0 mIU/mL, the MTX success rate was 75.0%. Fewer patients needed UAE or a laparotomy compared to patients with hCG values higher than 17757.0 mIU/mL (P = 0.007). In patients with a GS size less than 10.4 mm, the MTX success rate was 80.0%. Fewer patients among them needed UAE or a laparotomy compared to those among patients with a GS size greater than 10.4 mm (P = 0.089). In patients with hCG values and GS sizes lower than the cut-off values, the MTX success rate was 80.0%. Fewer patients among them needed UAE or a laparotomy compared to those among patients with hCG values and/or GS sizes higher than the cut-off values, respectively (P = 0.010). Conclusion: Patients with hCG values less than 17757.0 mIU/mL and GS sizes less than 10.4 mm may have a greater chance of successful systemic MTX treatment when it is used as the first line of treatment for CSP.